Pre-harvest spray application of prohexadione-calcium and paclobutrazol improves rind colour and regulates fruit quality in M7 Navel oranges - Rehman, M.; Singh, Zora; Khurshid, T. (Elsevier, 2018)
Sweet orange (Citrus sinensis L. Osbeck) cv. ‘M7’ Navel exhibits poor flavedo colour at harvest in Western Australia. Gibberellins are known to retard fruit colour development in citrus fruit, therefore the efficacy of different concentrations and timings of spray applications of two inhibitors of gibberellin biosynthesis such as prohexadione calcium (Pro-Ca) and paclobutrazol (PBZ) on flavedo colour development and fruit quality was investigated. The effects of an aqueous solution containing different concentration of Pro-Ca (200, 400, 600, 800, 1200, 1600 or 2000 mg L−1), and PBZ (100, 250, 500, 1000, 1500 and 2000 mg L−1) sprayed at 6 or 3 weeks before anticipated harvest (WBAH) on flavedo colour development particularly from yellow to deep orange and on the fruit quality were investigated during 2015 and 2016. Unsprayed trees were kept as control. The spray application of Pro-Ca (800 mg L−1) resulted in decreased hue angle (h°) (57.5), and increased citrus colour index (CCI) (10.2) and, total carotenoid levels (38.3 mg kg−1) in the flavedo during 2015. Furthermore, Pro-Ca (600 or 800 mg L−1) showed enhanced levels of total carotenoids (39.2 and 38.3 mg kg−1) respectively, during 2015. In 2016, a single spray application Pro-Ca (1200 mg L−1) at 3 WBAH exhibited reduced h° (56.6) and increased CCI (10.7), and levels of total carotenoids (36.8 mg kg−1) as compared to the control. Additionally, a single spray application of Pro-Ca (800, 1200 or 1600 mg L−1) was able to increase total carotenoids in the flavedo (32.7, 36.8 or 33.1 mg kg−1) respectively. In 2016, Pro-Ca (800 mg L−1) exhibited increased SSC (13.0%) and reduced TA (1.08%) in the fruit juice. A single spray application of PBZ (1000 mg L−1) at 6 WBAH significantly reduced h° (56.7) and increased CCI (10.6) and levels of total carotenoids in the flavedo (42.6 mg kg−1). However, a single spray application of PBZ (1500 mg L−1) at 3 WBAH showed lower h° (55.4) and enhanced CCI (11.2) and level of total carotenoids (47.1 mg kg−1) in the flavedo during 2016. In conclusion, pre-harvest spray application of Pro-Ca (800 and 1200 mg L−1) applied at 6 and 3 WBAH respectively enhanced fruit colour. A single pre-harvest spray application of PBZ (1000 and 1500 mg L−1) applied at 6 and 3 WBAH respectively improved fruit colour in early maturing ‘M7’ Navel.